2007
DOI: 10.1007/s10557-007-6076-5
|View full text |Cite
|
Sign up to set email alerts
|

Trimetazidine Protective Effect Against Ischemia-Induced Susceptibility to Ventricular Fibrillation in Pigs

Abstract: TMZ limited ischemia-induced electrical dysfunction leading to cardiac susceptibility to VF by decreasing lipid peroxidation and maintaining ionic homeostasis. TMZ could therefore provide protection against ischemia-induced VF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…At the cellular level, TMZ preserves ATP production, reduces the generation of oxygen free radicals (Maupoil et al, 1990;Gambert et al, 2006;Kutala et al, 2006), and reduces intracellular acidosis and calcium overload (Kantor et al, 2000). TMZ has been shown to protect hearts from ischemia-induced electrical dysfunction leading to ventricular fibrillation (Vaillant et al, 2008), ischemia-reperfusion-induced damage to mitochondrial respiration (Guarnieri and Muscari, 1993), and ischemia-reperfusion injury by decreasing myocardial lactate content early at reperfusion (Pantos et al, 2005). Tritto et al (2005) demonstrated that TMZ attenuated tissue injury in postischemic hearts by inhibiting the activation of neutrophils.…”
Section: Preconditioning Of Mscs With Trimetazidine For Cell Therapy 547mentioning
confidence: 99%
“…At the cellular level, TMZ preserves ATP production, reduces the generation of oxygen free radicals (Maupoil et al, 1990;Gambert et al, 2006;Kutala et al, 2006), and reduces intracellular acidosis and calcium overload (Kantor et al, 2000). TMZ has been shown to protect hearts from ischemia-induced electrical dysfunction leading to ventricular fibrillation (Vaillant et al, 2008), ischemia-reperfusion-induced damage to mitochondrial respiration (Guarnieri and Muscari, 1993), and ischemia-reperfusion injury by decreasing myocardial lactate content early at reperfusion (Pantos et al, 2005). Tritto et al (2005) demonstrated that TMZ attenuated tissue injury in postischemic hearts by inhibiting the activation of neutrophils.…”
Section: Preconditioning Of Mscs With Trimetazidine For Cell Therapy 547mentioning
confidence: 99%
“…It is also known that long‐term treatment with TMZ alleviates the myocardial accumulation of the oxidation reactive form and prevents lipid per‐oxidation . It improves the activity of the superoxide dismutase (an antioxidant enzyme) and relieves the oxidative stress phenomena . TMZ used in standard pharmacological therapy and in a domiciliary exercise programme improves a functional performance in patients with peripheral arterial diseases .…”
Section: Introductionmentioning
confidence: 99%
“…[10] It improves the activity of the superoxide dismutase (an antioxidant enzyme) and relieves the oxidative stress phenomena. [11,12] TMZ used in standard pharmacological therapy and in a domiciliary exercise programme improves a functional performance in patients with peripheral arterial diseases. [13,14] Although TMZ is mainly applied to prophylaxis and therapy of cardiovascular diseases, it is also used in the case of patients with ischemic heart diseases and stable angina or acute coronary syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…TMZ: HS and resuscitation, TMZ at a 10 mg/kg dose. 16 HTK: HS and resuscitation, HTK administered intravenously at a constant rate. 17 ALO: HS and resuscitation, ALO at a 50 mg/kg dose.…”
Section: Study Groupsmentioning
confidence: 99%